Encryption Implementation Paradigm for Digital Resource Management–An Overview - Kingsley O, Igboji,; Gabriel E, Ugwu (IJRDO -Journal of Computer Science Engineering, 2017)
Encryption is a process that “scrambles” data using sophisticated mathematical equations in order to protect it and keep it private. This process transforms or encodes data in any form such as text, audio, video, graphics etc into another form it will be difficult to understand or interpret. Frequent illegal retrieval and utilization of digital resources as enumerated above arouse the quest for a competent security artifact to eradicate the menace. Encryption key is not mere strings of text like passwords but are essentially blocks of gibberish, thus requires a safe means to pass the key across to end users. Implemented algorithms encrypts original piece until interested users meet certain obligations before access is granted with a decipher key. Research over the years adjudged this approach as a well structured routine in managing digitally embedded resources. A scenario facilitated by utilizing IP authentication, digital certificate, signature and watermarking mechanisms to abate the rake been meted on digital resources. Encryption ostensibly creates a paradigm driven by evolving technological world.